Characterization of p-GaN1−xAsx/n-GaN PN junction diodes - Qian, H.; Lee, K.B.; Vajargah, S.Hosseini; Novikov, S.V.; Guiney, I.; Zhang, S.; Zaidi, Z.H.; Jiang, S.; Wallis, D.J.; Foxon, C.T.; Humphreys, C.J.; Houston, P.A. (IOP Publishing, 2016)
The structural properties and electrical conduction mechanisms of p-type amorphous GaN1−xAsx/n-type crystalline GaN PN junction diodes are presented. A hole concentration of 8.5×1019 cm−3 is achieved which allows a specific contact resistance of 1.3×10−4 Ω cm2. An increased gallium beam equivalent pressure during growth produces reduced resistivity but can result in the formation of a polycrystalline structure. The conduction mechanism is found to be influenced by the crystallinity of the structure. Temperature dependent current voltage characteristics at low forward bias (<0.35 V) show that conduction is recombination dominated in the amorphous structure whereas a transition from tunneling to recombination is observed in the polycrystalline structure. At higher bias, the currents are space charge limited due to the low carrier density in the n-type region. In reverse bias, tunneling current dominates at low bias(<0.3 V) and recombination current becomes dominant at higher reverse bias.